Synergies among different parts of sustainable development - Art Kovacic (African Journal of Environmental Economics and Management, 2013)
Sustainable development became an important paradigm in new EU countries. In new member countries can be seen the development of tools for measuring sustainable development. Sustainable development can be measured on many ways. In the paper we will show the evaluation of main determinants of sustainable development. Normally more developed countries have a higher sustainability readiness. In the paper the next hypothesis will be tested: First hypothesis: we need a wider set of sustainable development indicators, if we want to measure synergies among different parts of sustainable development. Second hypothesis: land used policies have an important influence on sustainable development. Third hypothesis: by analysing the indexes of sustainable development we can find the main development steps for improving our position. In the paper it will be shown why we must analyse different parts of sustainable development. Sustainable development is usually measured by the system of indicators. We must take into account also the paradigm of the knowledge based economy. The creation of a knowledge-based economy and society, and the preparation of respective action plans presuppose that the situation of the developed economies be analysed and give deeper insights into the current basis of economic development gained. Only this basis can serve the planning of future in a way that would guarantee rapid economic development and the harmonisation of the average wage level with that of the European Union. This entails both economic and social objectives, according to which Europe seeks to become the most competitive and dynamic knowledge- based economy in the world, capable of sustainable economic growth with more and better jobs, and a better social cohesion.